Analysis of the factors affecting the dimensional accuracy of 3D printed products - Tiwari K.; Kumar S. (My University, 2025)
3D printing or additive manufacturing is a process in which objects are made by adding material instead of removing it. It is printed layer by layer in a machine known as 3D printer which uses the digital file to convert the virtual design of the object to a real one. Its scope as a manufacturing process is increasing rapidly and has the potential to replace conventional manufacturing processes. The focus now shifts to make it the primary manufacturing process and for this the most important point to look upon is the accuracy of 3D printed products. This research works intend's to study the factors which effect's the dimensional accuracy of the parts produced by 3D printing. Fused Deposition Modelling (FDM) is the method that is used in this study and the material used is Polylactic acid (PLA) filament. Factors which are observed are the effect of orientation, i.e. the effect of gravity on the accuracy of 3D printed products, and the effect of support which shows how the accuracy can differ when the support feature is enabled. © 2018 Elsevier Ltd. All rights reserved.